Functional and Self-Congruity's influence on lodging choice: A comparison of franchise and independent accommodations. (March 2022) - Boley, B. Bynum; Russell, Zachary A.; Woosnam, Kyle M.
Abstract: Increasingly, guests are choosing accommodations not solely for the functional service quality they provide, but on the experiential and symbolic aspects of lodging stays. While some have begun to compare the influence of functional and self-congruity on lodging choice, there has yet to be a comparison between franchise and independent accommodations. This research compares the influence of functional and self-congruity on intent to choose franchise and independent accommodations. Results reveal that for a sample of 623 U.S. travelers, the decision to choose a franchise or independent accommodation is influenced by both functional and self-congruity. However, the influence of self-congruity on likelihood to stay was greater for independent accommodations than franchise accommodations, signifying that the symbolic aspects of staying at an accommodation are much stronger for independent accommodations. Other analyses such as paired samples t-tests and qualitative word clouds confirm that the two lodging categories are distinct offerings within consumers' psyche.